House finch-associated Mycoplasma gallisepticum responsible for epizootic conjunctivitis in passerines - Taiyari, Hossein; Abu, Jalila (Universiti Putra Malaysia Press, 2020)
In 1994, Mycoplasma gallisepticum (MG) was reported to be responsible for conjunctivitis outbreak in the North American house finch population. This new course of MG infection in passerine was the result of spillover infections from the poultry strains. In severe cases of the disease, the conjunctival lesions might cause blindness and death, but in the mild form, there is a chance of recovery. The immune system of the recovered birds develops a resistance to the previous strains. However, the incomplete immune responses and the ability of MG to rapidly alter its surface antigens allow the pathogen to evolve new strains that can infect the birds that have already developed immune resistance. Although the rate of mortality decreases as a result of developing resistance, the persistence of the disease continues due to the increase in both virulence and the replication rate of the new strains. Therefore, the morbidity rate has remained steady, and new species of birds become infected as a result of evolutionary adaptation of the new strains. In this regard, the objective of this study is to provide a review of the mycoplasma conjunctivitis in passerine species, notably by looking at it from the host-pathogen interaction point of view.